EduGame Sejarah Islam Masuk Indonesia - Dian Imam Nurrahim; Endah Sudarmilah (PROtek : Jurnal Ilmiah Teknik Elektro, 2016)
A game is a fun diversion, not a couple of children who are dependent on the game. With the presence of a few hypotheses about the happening to Islam to Indonesia, among others, Gujarat hypothesis, the hypothesis of Makkah, and after that, to the Persian hypothesis, the creator will make an instructive game based multiplatform utilize application build 2 with prizes that clarify these speculations. The reason for this study to draw the consideration of primary school understudies to help study material Islamic entered Indonesia history. This study utilizes SDLC (frameworks improvement life cycle) containing the means of requirement, designing, coding and implementation. The consequences of this study are the games with the material history of Islam entered Indonesia that can be played on desktop and smartphone.Â